1981
DOI: 10.1111/j.1699-0463.1981.tb00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Human Epithelial Cell Line With Special Reference to Its Ultrastructure

Abstract: A commercially available cell line (NCTC 2544) originating from presumably normal human skin was chosen as an in vitro model system for subsequent studies of the effects of different agents on human epithelial cells. The cell line, therefore, was ultrastructurally and otherwise characterized at intervals by techniques which allow standardized controls of the model. The cell line was classified as epithelial both by phase contrast microscopy and transmission electron microscopy. The cells were polygonal, fully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Previous studies have found fibroblasts (embryonic origin) to be more sensitive than keratinocytes (epidermal origin). Benavides et al (2004a), Clothier et al (1999, Ree et al (1981) and Boukamp et al (1988) describe a higher resistance of keratinocytes, which is associated with their anatomical position, as they are constantly exposed to external aggression.…”
Section: Cytotoxicity In 3t3 Fibroblasts and Hacat Keratinocytesmentioning
confidence: 99%
“…Previous studies have found fibroblasts (embryonic origin) to be more sensitive than keratinocytes (epidermal origin). Benavides et al (2004a), Clothier et al (1999, Ree et al (1981) and Boukamp et al (1988) describe a higher resistance of keratinocytes, which is associated with their anatomical position, as they are constantly exposed to external aggression.…”
Section: Cytotoxicity In 3t3 Fibroblasts and Hacat Keratinocytesmentioning
confidence: 99%
“…the cells were subcultured in Fdcon plastic tissue culture flasks (75 cm2) containing 13 ml Dulbecco's modified Eagle's culture medium supplemented with 2% foetal calf serum, 12% horse serum and antibiotics. The present study was carried out simultaneously with that previously reported ( 7 ) and the same serum lots were used.…”
Section: Cell Culturementioning
confidence: 98%
“…The cells were fixed as described previously ( 7 ) and photographed as a monolayer on Tyrode buffer. One thousand cells from cultures fixed 2 hours, 3 days and 6 days after PUVA exposure were scored for the number of nuclear elements per cell.…”
Section: Phase Contrast Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…followed by centrifugation at 1146 g for 15 min. Apart from unimportant details the cells were further processed as previously described by us (Ree et al 1981a). In short the cells were postfixed in 1 % buffered osmium-tetroxide, dehydrated, embedded in Epon 812, cut with a diamond knife and post-stained with uranyl acetate and lead citrate.…”
Section: Transmission Electron Microscopymentioning
confidence: 99%